IMPLEMENTASI KEBIJAKAN PENGEMBANGAN SARANA AIR BERSIH KAWASAN PERDESAAN DI DESA INSIL KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - LANGITAN, CHIKITA PONTICHA; LALOMA, ALDEN; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2020)
Abstract : This study aims to find out about the implementation of clean water facility development policies in rural areas in Insil Village, Passi Timur District, Bolaang Mongondow Regency. Type of qualitative descriptive research. All data presented is in accordance with primary and secondary data. Data collection techniques based on observation, interviews and documentation. Data obtained from various sources were analyzed and conclusions were drawn. The problem in this research lies in the implementation of the policy of developing clean water facilities that have not been running optimally so that some people still have difficulty getting clean water. The findings of this study indicate that the implementation of clean water facility development policies in rural areas in the Insil Village of Passi Timur sub-district Bolaang Mongondow can be seen from the indicators of this research that communication, resources, disposition and bureaucratic structure have not been fully implemented. The communication process that occurs in the implementation of clean water facility development policies to the lack of support by the apparatus resources in implementing clean water facility development policies causes the implementation of these policies to not be carried out effectively. The village government need to conduct direct socializatio of programs or activities carried out related to the development of clean water facilities as well as improvements in coordination between relevant organizations or institutions and increase information regarding the implementation of clean water facility development policies. Keywords : Policy Implementation, Development, Clean Water Facilities, Rural Areas.